Effectiveness of perches in promoting bird-mediated seed dispersal for natural forest regeneration: a systematic review - Jelaine L. Gan; Matthew J. Grainger; Mark David Foster Shirley; Sheena Davis; Molly Watson; Shreya Dube; Marion Pfeifer (Environmental Evidence)
Abstract Background Assisted Natural Regeneration (ANR) is an increasingly popular cost-effective approach to restore forests for climate change mitigation and biodiversity conservation. One ANR strategy is the use of perches to attract avian seed dispersers to degraded landscapes for increased seed supply and seedling establishment. This systematic review sought to determine the effectiveness of artificial, semi-natural, and natural perches in promoting natural forest regeneration, specifically in driving four outcomes: seed richness, seed density, seedling richness, and seedling density. Methods In September 2023, we searched for studies in eight bibliographic sources, which include an organizational library and a web-based search engine, using a refined search string in English. After deduplication, we conducted double screening at title and abstract, then at full text level to check for eligibility (e.g., compared perches versus control). The final list of studies underwent critical appraisal based on risk of bias and method validity, then data extraction. We used Hedges’ g as our effect size and fitted each outcome in a three-level meta-regression model. We also tested the effect of matrix type, bioregion, and precipitation variation as modifiers, and conducted sensitivity analysis based on risk of bias and method validity. Review findings After screening, we accepted a total of 396 studies in 79 articles for the review. The majority of these studies examined seed (49%) and seedling density (28%) outcomes over richness, using mostly natural perches (68%) and, to a lesser frequency, artificial and semi-natural perches. Most studies that included distance to forest edge as a factor reported no effects (n = 68). We then analysed 333 studies in a meta-analysis. Results showed that natural perches had overall positive effects in increasing seed and seedling density and richness, while artificial and semi-natural perches were effective only for seed outcomes. We found high heterogeneity in our models, with perch effectiveness affected by matrix type, bioregion, precipitation variation, method specificity, as well as study quality. In general, perches showed robust positive effects in shrublands and grasslands in tropical, subtropical, and mediterranean biomes. Conclusions The use of perches can be an effective ANR strategy to increase seed rain and seedling establishment in a variety of degraded landscapes. We recommend that natural perches be preserved in the matrix, but in areas lacking these natural features, to explore the use of artificial or semi-natural perches to increase seed rain and follow it up with additional treatments, such as soil amelioration and weeding, to improve seedling establishment. Due to insufficient data, we could not analyse the effect of distance to forest edge as a moderator in our meta-regression models. This gap can be addressed by examining perches placed at increasing distances from the edge and having better data sharing practices. We also emphasize a need for improving the quality of reporting, such as variances and detailed methodologies, in order for research to be useful for systematic reviews and meta-analysis.